Case report: Open-heart removal for a cement embolism formed 10 years ago in the right ventricle and pulmonary artery - Liu, XinPei; Chu, PeiShan; Miao, Qi (Frontiers in Cardiovascular Medicine, 2023)
Bone cement embolism is a known complication of kyphoplasty operation. Cement embolisms without immediate fatal complication like cardiac perforation or hypoxemia were often stable during observation. We report a large volume bone cement embolism involving the right ventricle and the pulmonary artery system. The patient developed mild exertional short of breath and chest pain after a percutaneous kyphoplasty operation 10 years ago. However, her mild symptoms were attributed to multiple myeloma and no chest imaging was taken until the symptoms exacerbated after a COVID-19 infection 6 months ago. A large, tree-branch-shaped embolus was found, causing severe obstruction of the ascending and middle-lobe branch of the right pulmonary artery. Pulmonary perfusion scintigraphy demonstrated impared perfusion of the right upper and middle lobe. An open-heart removal was performed, and the symptoms were relieved afterwards. We report this case to highlight the importance of routine chest imaging after PKP operation, and to claim that open-heart removal for chronic cement pulmonary embolism is technically feasible and safe.